Simultaneous quantitation of 17 endogenous adrenal corticosteroid hormones in human plasma by UHPLC-MS/MS and their application in congenital adrenal hyperplasia screening - Zhang, Qiaoxuan; Zhan, Min; Wu, Huihui; Feng, Pinning; Jin, Xing; Wan, Zemin; Yan, Jun; Zhang, Pengwei; Ke, Peifeng; Zhuang, Junhua; Zhou, Jiuyao; Han, Liqiao; et al. (Frontiers in Chemistry, 2022)
Accurate investigation of adrenal hormone levels plays a vital role in pediatric endocrinology for the detection of steroid-related disorders. This study aims to develop a straightforward, sensitive UHPLC-MS/MS method to quantify 17 endogenous adrenal corticosteroid hormones in human plasma. These hormones are the main ingredients in the synthetic and metabolic pathways of adrenal corticosteroid hormones. Chromatographic separation was achieved on a C18 column before electrospray ionization triple-quadrupole mass spectrometry in multiple reaction monitoring mode with a run time of 7 min. The samples were extracted by liquid-liquid extraction and required no derivatization. Analytical performance was evaluated, including linearity, analytical sensitivity, accuracy, precision, and specificity. Plasma specimens from 32 congenital adrenal hyperplasia (CAH) patients and 30 healthy volunteers were analyzed to further reveal the diagnostic value of multiple steroid hormones in the synthetic and metabolic pathways of adrenal corticosteroid in CAH diagnosis. All hormones were effectively extracted and separated using our method. The method was essentially free from potential interference of isomers or structural analogues. The imprecisions were <10%. The lower limits of quantification varied from 0.05 to 15.0 ng/ml. Good linearity coefficients (r2 > 0.998) were also obtained for most hormones in the required concentration range, except for 21-deoxycortisol (r2 = 0.9967) and androstenediol (r2 = 0.9952). The recoveries for the steroid hormones ranged from 91.7 to 109.8%. We developed the UHPLC-MS/MS method for the simultaneous measurement of steroid hormones. The results showed that measurement of steroid hormones simultaneously could improve the diagnostic efficiency of CAH.